Incidence of digital adaptive learning programs on academic results in mathematics - Bravo, Richard Eduardo Sánchez; Gámez, María Rodríguez (International research journal of management, IT and social sciences, 2022)
This research aimed to analyze the incidence of digital adaptive learning programs in the academic results of the students of the seventh year of basic general education in the area of mathematics. Deductive and inductive methods were used which allowed analysis of the state of the art on adaptive learning programs due to its relevant formality for the review of scientific literature, to support this research work, the theoretical contributions of several authors on the themes of adaptive learning programs, the Aleks artificial intelligence program, the use of technology as an educational resource and the academic performance of students in the teaching-learning process and the cross-sectional analytical method was used that allowed the collection of data through Through the survey technique, the population studied was 11 teachers and 105 students who attended the seventh year of basic general education of the 2021-2022 school year from four educational units in the city of Chone.